2020
DOI: 10.48550/arxiv.2007.00533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partial Recovery in the Graph Alignment Problem

Abstract: In this paper, we consider the graph alignment problem, which is the problem of recovering, given two graphs, a one-to-one mapping between nodes that maximizes edge overlap. This problem can be viewed as a noisy version of the well-known graph isomorphism problem and appears in many applications, including social network deanonymization and cellular biology. Our focus here is on partial recovery, i.e., we look for a one-to-one mapping which is correct on a fraction of the nodes of the graph rather than on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…Interestingly, our proof relies on establishing an asymptotically matching lower bound to the mutual information I(π; A, B). This significantly deviates from the existing results in [HM20] based on Fano's inequality: P {overlap( π, π) ≤ δ} ≥ 1 − I(π;A,B)+1 log(n!/m) with m = |{π : overlap(π, π) ≥ δ}|, followed by applying the simple bound (6).…”
Section: Negative Results On Partial Recoverycontrasting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, our proof relies on establishing an asymptotically matching lower bound to the mutual information I(π; A, B). This significantly deviates from the existing results in [HM20] based on Fano's inequality: P {overlap( π, π) ≤ δ} ≥ 1 − I(π;A,B)+1 log(n!/m) with m = |{π : overlap(π, π) ≥ δ}|, followed by applying the simple bound (6).…”
Section: Negative Results On Partial Recoverycontrasting
confidence: 87%
“…Capitalizing on this key finding and applying the Chernoff bound together with a union bound over π ′ yields our tight conditions. We remark that the partial recovery results in [HM20] are obtained by analyzing an estimator slightly different from the MLE and the same MGF bound (15) is used. However, there are two major differences that led to the looseness of their results.…”
Section: Positive Results On Partial and Almost Exact Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that the partial recovery can be attained in polynomial time by a neighborhood tree matching algorithm in the sparse graph regime where nps ∈ (1, λ 0 ] for some constant λ 0 close to 1 and s ∈ (s 0 , 1] for some constant s 0 close to 1. More recently, the partial recovery is shown to be information-theoretically impossible if nps 2 log 1 p = o(1) when p = o(1) [HM20]. In contrast to the aforementioned work focusing on the estimation problem, our paper studies the hypothesis testing aspect of graph matching.…”
Section: Connection To the Literaturementioning
confidence: 99%